History and Status of Selected Hosts of the Ralstonia solanacearum Species Complex Causing Bacterial Wilt in Brazil - Lopes, Carlos A.; Rossato, Maurício (Frontiers in Microbiology, 2018)
Bacterial wilt induced by the Ralstonia solanacearum species complex is endemic to Brazil, where it can cause variable losses in many hosts. Its economic importance, however, cannot be precisely measured due to Brazil’s continental size, subject to variable weather conditions which directly affect disease expression. The objectives of this paper were (i) to gather scattered information on historical facts; (ii) to show the current distribution of the pathogen in the country, and (iii) to comment on future trends on the importance of the disease in economically important current and potential hosts, based on the pathogen’s variability and the global climate change under way.